Lebanese Shi'ite leadership, 1920-1970s : personalities, alliances, and feuds - Nir, Omri (Palgrave Macmillan, 2020)
Contents: Main classes in the traditional Lebanese Shi'ite community -- The centers of power -- The speakership of the Parliment -- The intellectuals and the power centers -- The decline of the Zuʻama.